Influence of Climatic Factors on Rainfed Rice Productivity in Sekotong Barat Village - Hari, Muhammad Akbar; Hayati, Hayati; Sjah, Taslim (PT FORMOSA CENDEKIA GLOBAL, 2025)
Rainfed rice productivity in Sekotong Barat Village tends to be low and has not shown significant improvement in recent years. This condition is suspected to be influenced by changes in climatic elements such as air temperature, rainfall, humidity, and solar radiation. This study aims to determine: 1) The productivity of rainfed rice in Sekotong Barat Village, 2) The climatic conditions in Sekotong Barat Village, and 3) The climatic factors that affect rainfed rice productivity in the village. The study utilized secondary climate data from 2020 to 2023 and primary productivity data from 30 farmers. The analysis was conducted descriptively and quantitatively using multiple linear regression. The results showed that: 1) Rainfed rice productivity during the 2020-2023 period fluctuated, with a sharp decline in 2023, 2) Climatic conditions consisting of temperature (°C), rainfall (mm), air humidity (%), and solar radiation (%) experienced significant variations during the same period, 3) Statistically, none of the climatic factors had a significant effect-either simultaneously or partially-on rainfed rice productivity; however, temperature showed the most consistent influence in 2021 and 2022. These findings indicate that the rainfed rice farming system in this region is highly vulnerable to climate fluctuations. Therefore, appropriate climate-based adaptation strategies are needed, such as adjusting planting schedules, using climate forecasts, and adopting stress-tolerant rice varieties.